Health status, hospitalizations, day procedures, and physician costs associated with body mass index (BMI) levels in Ontario, Canada - Tarride JE; Haq M; Taylor VH; Sharma AM; Nakhai-Pour HR, O'Reilly D; Xie F; Dolovich L; Goeree R (Dove Medical Press, 2012)
Jean-Eric Tarride1,2, Mahbubul Haq1, Valerie H Taylor3, Arya M Sharma4, Hamid Reza Nakhai-Pour1, Daria O’Reilly1,2, Feng Xie1,2, Lisa Dolovich2,5,6, Ron Goeree1,21Programs for Assessment of Technology in Health (PATH) Research Institute, St Joseph’s Healthcare Hamilton, Hamilton, Ontario, Canada; 2Department of Clinical Epidemiology and Biostatistics, McMaster University, Hamilton, Ontario, Canada; 3Department of Psychiatry, University of Toronto, Ontario, Canada; 4Department of Medicine, University of Alberta, Edmonton, Alberta, Canada; 5Centre for Evaluation of Medicines, St Joseph’s Healthcare Hamilton, Hamilton, Ontario, Canada; 6Department of Family Medicine, Faculty of Health Sciences, McMaster University, Hamilton, Ontario, CanadaBackground: Obesity is today’s principal neglected public health problem, as a rising proportion of adults will succumb to the medical complications of obesity. However, little is known about the burden of obesity in adults living in Ontario.Objectives: To present an overview of the human and economic burden associated with BMI categories in Ontario, Canada, in terms of socio-demographics, comorbidities, health-related quality of life (HRQoL) and costs associated with hospitalization, same day procedures and physician visits.Methods: The records of all Ontarians who participated in the Canadian Community Health Survey (CCHS), cycle 1.1 and provided consent to data linkage were linked to three administrative databases. Socio-demographic variables, medical characteristics, HRQoL, one year hospitalization, day procedure and physician costs were described per BMI category. Regression analyses were conducted to identify predictors of medical characteristics, HRQoL and costs.Results: More than 50% of adult participants were either overweight or obese in 2000/2001. Obese adults, and to a lesser extent overweight adults, were more likely to report physician-diagnosed comorbid conditions, to use medications, and to have a lower HRQoL. After covariate adjustment, the hospitalization and physician costs were respectively 40% and 22% higher among obese and overweight adults than among normal-weight adults. No statistical cost differences were observed between normal and underweight individuals or between normal and overweight individuals. HRQoL was significantly lower in underweight and obese adults when compared to normal-weight individuals.Conclusions: Due to the large human and economic burden associated with under- or excess-weight, policies promoting healthy weight should remain a priority for governments and employers.Keywords: health-related quality of life, costs, body mass index categories, Ontario